Analysis of Supporting Factors Associated with Exclusive Breastfeeding Practice in the Urban Setting during the COVID-19 Pandemic - Agrina Agrina; Dedi Afandi; Suyanto Suyanto; Erika Erika; Yulia Irvani Dewi; Siska Helina; Dita Pramita; Nanda Safira (MDPI AG, 2022)
Breastfeeding mothers have had limited access to breastfeeding support throughout the COVID-19 pandemic. This study aims to investigate breastfeeding practices during the COVID-19 period and to determine the factors associated with supporting exclusive breastfeeding. A sequential explanatory mixed methods approach was adopted, including a quantitative method in the first phase and qualitative method in the second phase. Mothers whose babies were aged over 6 months to 24 months old from July to September 2021 in Pekanbaru City were selected as research subjects. Data analysis was performed with multivariate and deductive content analysis. Of 156 participants, 97 mothers (62.2%) exclusively breastfed their babies. Of those, mothers who delivered exclusive breastfeeding worked less than eight hours per day, were aged 17-25 and had low education. Though by using exclusive breastfeeding practice as a reference, associated supports, including emotional, instrumental, appraisal and information regarding exclusive breastfeeding practice were insignificant; however, mothers who practice exclusive breastfeeding had higher information support. During the COVID-19 pandemic period, the informational support factor was found to be important to achieve the successful exclusive breastfeeding practice.